2020
DOI: 10.3390/min10111012
|View full text |Cite
|
Sign up to set email alerts
|

REE Geochemical Characteristic of Apatite: Implications for Ore Genesis of the Zhijin Phosphorite

Abstract: Phosphorite-type rare earth deposits, which are one of the important types of rare earth elements (REE) ore deposits, have attracted increasing attention because of the extreme enrichments in heavy rare earth elements (HREE), including Yttrium (Y). In this study, in situ geochemical analyses of apatite grains from Zhijin phosphorites were conducted using electron probe microanalysis (EMPA) and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS). Based on EPMA mapping analysis, we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…It was also found that the REEs in phosphate rock mainly occur in dolomite and apatite, and exist in the form of the isomorphism phase (Xiqiang et al . 2020). Compared with the primary phosphate rock, the diffraction peak intensity of dolomite and apatite in the abiotic control group did not significantly decrease, indicating that dolomite and apatite still exist in the tailings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also found that the REEs in phosphate rock mainly occur in dolomite and apatite, and exist in the form of the isomorphism phase (Xiqiang et al . 2020). Compared with the primary phosphate rock, the diffraction peak intensity of dolomite and apatite in the abiotic control group did not significantly decrease, indicating that dolomite and apatite still exist in the tailings.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4(a) shows that the mineral composition of primary phosphate rock is relatively simple, and mainly composed of dolomite and apatite, and no independent rare-earth minerals have been found. It was also found that the REEs in phosphate rock mainly occur in dolomite and apatite, and exist in the form of the isomorphism phase (Xiqiang et al 2020). Compared with the primary phosphate rock, the diffraction peak intensity of dolomite and apatite in the abiotic control group did not significantly decrease, indicating that dolomite and apatite still exist in the tailings.…”
Section: X-ray Diffraction Analysismentioning
confidence: 93%
“…By comparing the contents of major elements and REEs in natural phosphorite, flotation concentrate, and leaching concentrate, the separation effect can be judged. Studies have shown that the contents of REEs increased with the increase of Fap content, 9,29 but there was no evidence to suggest that it increased with the increase of Dolo content 30 . It was currently recognized that REEs mainly replace calcium atoms in Fap in the form of isomorphism, 31,32 and the content of REEs was often positively correlated with the content of Fap.…”
Section: Methodsmentioning
confidence: 99%
“…It was urgent to find a RE reserve resource to meet the needs of industrial production (Batapola et al, 2020;Ji and Zhang, 2021). Phosphate contained all Lanthanides except Pm, in which the content of ΣRE (the total RE) was 1098~1688 ppm (Xiqiang et al, 2020). From this perspective, phosphate was a reserved RE resource and had great development value.…”
Section: Introductionmentioning
confidence: 99%